The Ascension of Thought and Action (Maironis’ Kame Išganymas) - Jonaitis, Marijus (Sociologija. Mintis ir veiksmas, 1997)
The aim of the article is to develop an interpretation of sociological and philosophical ideas in Maironis’ “Kame išganymas”. The author suggests that Maironis’ work might be read as a discussion of the interrelation between the horizontal life chances and the vertical forms of social relations. On these grounds the author argues that the work is an effort to disclose the connection between culture and social practices that provides the grounds to discuss a sociological problem of an empowering culture.